Ownership, sovereignty and global governance - David Williams (University of Oxford, Global Economic Governance Programme (GEG), 2006)
In recent years western aid agencies have come to embrace the language and practices of "ownership". This signals a shift away from conditionality as the dominant mode of relationship between these agencies and recipient states. The principle concern of this paper is to locate this shift in the changing international political context. It argues that we should see "ownership" as intimately connected to an expanding global governance regime. Seen in this way the stress on "ownership" reflects a concern to configure and reconfigure patterns of governance. The emergence of a global governance regime has important implications for our understanding of development and for the future of political accountability in developing countries.
Keywords: 330